2017
DOI: 10.1007/s12070-017-1195-1
|View full text |Cite
|
Sign up to set email alerts
|

Second Branchial Anomalies: A Study of 94 Cases

Abstract: Ninety-four patients with second branchial anomalies were retrospectively analysed at a tertiary care centre from January 2006 to September 2016 to determine the demographical data and management. Branchial sinus and fistula presented earlier as compared to branchial cyst. The mean age at presentation in case of branchial sinuses, fistulae and cysts was 5.07, 5.79 and 7.31 years respectively. There was preponderance in males as compared to females, more so in bilateral cases. Male to female sex ratio was 2.91:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
(16 reference statements)
0
9
0
Order By: Relevance
“…Pediatric presentations are exceptional [ 16 , 24 , 27 ]. Symptoms are frequently insignificant and related to mass size with main presentation being sense of throat lump eventually leading to dysphagia or odynophagia without an external neck swelling [ 18 , 20 , 25 , 32 ]. Unusually, Saussez et al [ 29 ] reported a case with one-year history of snoring and no dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric presentations are exceptional [ 16 , 24 , 27 ]. Symptoms are frequently insignificant and related to mass size with main presentation being sense of throat lump eventually leading to dysphagia or odynophagia without an external neck swelling [ 18 , 20 , 25 , 32 ]. Unusually, Saussez et al [ 29 ] reported a case with one-year history of snoring and no dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…In case of unilateral, the right side preponderance is described. 5 Fistulography and computed tomography (CT) fistulogram are the modality of choice for radiological diagnosis of second branchial arch fistula (Figure 1). 1,3,5 Fistulography (performed with opacifying the fistula with contrast media) delineates the fistulous tract extending from the external cutaneous opening at the lateral neck to the tonsillar fossa.…”
Section: Discussionmentioning
confidence: 99%
“…5 Fistulography and computed tomography (CT) fistulogram are the modality of choice for radiological diagnosis of second branchial arch fistula (Figure 1). 1,3,5 Fistulography (performed with opacifying the fistula with contrast media) delineates the fistulous tract extending from the external cutaneous opening at the lateral neck to the tonsillar fossa. 1,2 CT fistulogram with reformatted images demonstrates the fistulous tract as well as its relationship with important structures of the neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, conventional surgery using a large cervical incision was used to ensure complete removal. 10-31 However, the large cervical incision results in a prominent scar. In an attempt to reduce visible scars, newer techniques have been developed, such as endoscopic surgery 9,32-35 and the use of a retro-auricular hairline incision (RAHI).…”
Section: Introductionmentioning
confidence: 99%